A facile and efficient approach for hypertrophic scar therapy via DNA-based transdermal drug delivery. Issue 36 (3rd September 2020) - Jiang, Kai; Chen, Yunsheng; Zhao, Di; Cheng, Jin; Mo, Fangli; Ji, Bin; Gao, Chao; Zhang, Chuan; Song, Jie
Abstract : DNA-Fe NPs, a novel and efficient nanocarrier, improve DOX penetration and enhance scar-inhibiting effects for HS therapy. Abstract : The transdermal drug delivery approach has been considered a potential therapy for human hypertrophic scars (HSs) instead of current uncomfortable surgical excision, local injection and laser therapy. However, a facile and efficient drug delivery method is urgently needed to overcome the skin barrier of transdermal administration. Herein, we employed a DNA-Fe nanoparticle delivery system via Fe ion driven self-assembly to satisfy the requirement of transdermal administration for HS therapy. Doxorubicin hydrochloride (DOX) as one of the widely used anticancer drugs was employed to treat the hyperplasia of abnormal skin fibrous tissue. Both in vitro and in vivo experiments of the DOX loaded DNA-Fe nanoparticles (DOX@DNA-Fe NPs) were performed to demonstrate the penetration ability, rapid drug release, and scar-inhibiting effects. This facile and efficient approach for HS therapy via a DNA-based transdermal drug delivery system may provide more possibilities for the development of transdermal administration.